Sticky Platelet Syndrome: 35 Years of Growing Evidence - Kubisz, Peter; Holly, Pavol; Stasko, Jan (Seminars in Thrombosis and Hemostasis, 2019)
Since the identification of antithrombin deficiency by Egeberg in 1956, ongoing research in prothrombotic defects continues to progress. Interestingly, past research has predominantly focused on coagulation factors and not on other components of the hemostatic system. The possible role of platelet function defects in the development of thrombotic events was suggested for the first time in the late 1970s, when an increased platelet adhesiveness and aggregation after epinephrine (EPI) and adenosine diphosphate (ADP) was found in a group of patients with unexplained transient ischemic attack. Clinical evidence for other types of thrombotic events (e. g. myocardial infarction, ischemic stroke, optic neuropathy, and pregnancy-related complications) with similar laboratory findings was provided by several authors in the 1980s and 1990s, with Drs. Mammen and Bick undertaking key research. The familial occurrence was noted as well, and the term sticky platelet syndrome was introduced by Holliday in 1983 to describe the defect. The term in our present understanding describes a thrombophilic qualitative platelet disorder characterized by increased in vitro platelet aggregation after the addition of very low concentrations of ADP and/or EPI and an increased risk of thromboembolic (predominantly arterial) events. Although now recognized for 35 years, significant issues, namely its etiology, inheritance, epidemiology, and diagnostics, remain a matter of vigorous debate. The aim of this review is to summarize the history, key works, and present understanding of the syndrome and to outline present-day diagnostic and clinical problems and controversies.
Keywords: sticky platelet syndrome; platelet hyperaggregability; thrombophilia; platelet disorders; adenosine diphosphate; epinephrine